Adenoid Cystic Carcinoma of the Nasopharynx: A Case Report and a Discussion about Prognostic Factors and the Role of Local Treatments. Issue 2 (March 2013) - Elkholti, Youssef; Cosmidis, Alain; Ardiet, Jean Michel; Laffay, Lisa; De Bari, Berardino
Adenoid cystic carcinoma (ACC) is a rare epithelioid malignancy. It occurs most frequently in the salivary glands, while its localization in the nasopharynx is rare and few cases have been reported in the literature. We report the case of a 32-year-old woman presenting with ACC of the nasopharynx who was treated with surgery and adjuvant intensity-modulated radiation therapy (IMRT, total dose: 68 Gy) and concomitant chemotherapy (cisplatin 100 mg/m 2 on the first and 21st days of IMRT). During irradiation, the patient developed G1 dermatitis and G2 mucositis (RTOG). Clinical and instrumental reevaluation 17 months after the end of radiotherapy did not show any signs of relapse, and she did not show any sign of local mild-severe toxicity. Adjuvant radiotherapy after standard complete surgical resection seems to be effective and well tolerated and should be strongly considered in the multidisciplinary approach to this infrequent carcinoma.